Level of Job Satisfaction and Turnover Intention among Academicians - Yasir Hayat, Mughal; Abdul Halim, Busari; Mansoor Ahmed, Channa; Rehman Ullah, Khan; Zeeshan, Ahmad; Muhammad Zulqarnain, Safdar; Humaira, Naz; Muhammad Umar, Khan (Medwell Journals, 2016)
The aim of this study is to explain the unique role of motivation and job satisfaction and turnover intention by digging knowledge taken from different theories and models given by the different researchers and the measurement by different indicators. To understand the job satisfaction and turnover intention seems to be fragmented and tangled in many disciplines. To construct meaningful understanding of motivation and job satisfaction and turnover intention various disciplines were reviewed and synthesized were discussed. The aim of this study is to give the deeper understanding of underlying theories of motivationand job satisfaction and turnover intention. The literature that helps conceptualize the job satisfaction, urnover intention, second, the founding pieces of literature that composite the theory and third, the most emerging literature in the job satisfaction and turnover intention are selected to explain the job satisfaction and turnover intention. Based on thorough review of literature new conceptual studdy has been introduced. In both, the literature and organizational literature, the existing theories of job satisfaction and turnover intention can be evaluated to fully capture the distinctive aspects of the satisfaction various theories of satisfaction are encompassed. This extended literature requires empirical testing to identify the dimensions of the job satisfaction and motivation and turnover intention.The extended literature of job satisfaction and turnover will be useful to bring changes in the satisfaction level of the employees and helps the researchers to understand easily the theories of satisfaction and turnover.